2019
DOI: 10.3390/en12163102
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-Temporal Characteristics of the Driving Factors of Agricultural Carbon Emissions: Empirical Evidence from Fujian, China

Abstract: With the development of agricultural modernization, the carbon emissions caused by the agricultural sector have attracted academic and practitioners’ circles’ attention. This research selected the typical agricultural development province in China, Fujian, as the research object. Based on the carbon emission sources of five main aspects in agricultural production, this paper applied the latest carbon emission coefficients released by Intergovernmental Panel on Climate Change of the UN (IPCC) and World Resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 51 publications
1
43
0
Order By: Relevance
“…Additionally, the CH 4 emission of rice in different growth cycles can be affected by climate and hydrothermal conditions. Therefore, based on the existing calculation model of carbon emission coefficient [39], the CH 4 emission factors of rice in this paper was estimated according to the data on climate, soil, and hydrology in different provinces (see Table 2). Change (IPCC) and the greenhouse gas accounting method in China's "Guidelines for the Preparation of Provincial Greenhouse Gas Inventories (Trial)", the N 2 O in the atmosphere mainly comes from agricultural land, animal manure management, and the wastewater treatment processes of the waste treatment sector, among which more than 70% of the nitrogen emissions come from agricultural production.…”
Section: Carbon Emissions From Rice Cultivationmentioning
confidence: 99%
“…Additionally, the CH 4 emission of rice in different growth cycles can be affected by climate and hydrothermal conditions. Therefore, based on the existing calculation model of carbon emission coefficient [39], the CH 4 emission factors of rice in this paper was estimated according to the data on climate, soil, and hydrology in different provinces (see Table 2). Change (IPCC) and the greenhouse gas accounting method in China's "Guidelines for the Preparation of Provincial Greenhouse Gas Inventories (Trial)", the N 2 O in the atmosphere mainly comes from agricultural land, animal manure management, and the wastewater treatment processes of the waste treatment sector, among which more than 70% of the nitrogen emissions come from agricultural production.…”
Section: Carbon Emissions From Rice Cultivationmentioning
confidence: 99%
“…The output variables include gross value of planting output (in thousand CNY) and planting net carbon sink (in thousand tons of CO2-equivalent). The calculation formula, coefficient of agricultural carbon sink and carbon emission are based on the research of Tian et al (2014) [30]and Chen et al (2019) [31]. The main input variables of agricultural production are labor, land, machinery and fertilizer.…”
Section: Dependent Variablementioning
confidence: 99%
“…Based on the carbon emission sources of five main aspects in agricultural production, Chen, Li, Su, and Li [4] applied the latest carbon emission coefficients released by Intergovernmental Panel on Climate Change of the UN (IPCC) and World Resources Institute (WRI), and then used the ordered weighted aggregation (OWA) operator to remeasure agricultural carbon emissions in Fujian from 2008-2017. The research results showed that the regression coefficients of each selected factor in the cities were positive or negative, which indicated that the impacts on agricultural carbon emission had the characteristics of geospatial nonstationarity.…”
Section: Agricultural Carbon Emissionsmentioning
confidence: 99%